Ground-state cooling in cavity optomechanical systems - Wen, Pengyu; Wang, Min; Long, Gui-Lu (Frontiers in Physics, 2023)
The development of quantum optomechanics enables the manipulation of the quantum state of a macroscopic object and the conversion of frequency in different domains in quantum information processing, which prompts the process of quantum network and quantum computing. However, to enter the regime of quantum optomechanics, it’s necessary to prepare a mechanical object in its ground state. In this review, we briefly introduce the process of ground-state cooling in cavity optomechanical system. We first elucidate the theory of optomechanical cooling from both the classical and quantum perspective. Then we review experimental process about ground-state cooling in cavity optomechanical systems in these years, which includes the active feedback cooling and intrinsic optomechanical cooling. We selectively introduce the apparatus, samples and final cooling performance of some remarkable experiments. Finally, theoretical discussions on novel cooling approach will be reviewed, including cooling beyond resolved-sideband regime and multimode cooling, which may serve as a guidance for future experiment design.